Study of the Effect of Post Weld Heat Treatment on the Bending Strength of Weld Joints in SMAW and GMAW Methods in Root Bend Areas and Face Bend on ASTM A106 Grade B - Paskel, M. Piere Sam; Ariyon, Muhammad; Fitrianti, Fitrianti; Herawati, Ira; Sebayang, Alexander; Tarigan, Efrata; Idhamkamil, Idhamkamil; Tarigan, Liwat (International Journal of Engineering, Science and Information Technology, 2025)
This study evaluates the effect of Post Weld Heat Treatment (PWHT) on the bending strength of raw materials and welding joints using SMAW and GMAW welding methods. Tests were conducted on root and face bends to compare bending strength before and after PWHT treatment. The test results show that in the root bend area, the base material without PWHT has a bending strength of 3983.16 MPa, while in SMAW and GMAW welding, the bending strength is 3788.39 MPa and 2695.96 MPa, respectively. After PWHT was applied, the bending strength of the base material increased to 4739.76 MPa, while that of SMAW and GMAW welding increased to 4131.62 MPa and 5193.39 MPa, respectively. In the face bend area, the base material without PWHT showed a bending strength of 3077.70 MPa, with SMAW and GMAW welding producing bending strengths of 2654.28 MPa and 2259.32 MPa, respectively. After PWHT, the bending strength of the base material increased to 3289.05 MPa, while SMAW and GMAW welding recorded 2641.47 MPa and 3498.07 MPa, respectively. This study's results indicate that PWHT significantly improves bending strength, especially in the base material and weld joints in the root bend area.